Segmental coronary endothelial dysfunction in patients with minimal atherosclerosis is associated with necrotic core plaques. Issue 18 (3rd June 2009) - Lavi, S; Bae, J-H; Rihal, C S; Prasad, A; Barsness, G W; Lennon, R J; Holmes, D R; Lerman, A
Abstract : Background/objective: Endothelial dysfunction and atherosclerosis are systemic disorders, but are often characterised by segmental involvement and complications. A potential mechanism for local involvement early in the disease process may be related to plaque composition. This study was designed to test the hypothesis that in patients with minimal coronary atherosclerosis, coronary artery segments with abnormal endothelial function have specific plaque characteristics. Methods: Intravascular ultrasound (IVUS) images were obtained from 30 patients who underwent coronary endothelial function assessment. Spectral analysis of the IVUS radiofrequency data was used for assessment of plaque composition. IVUS findings of the coronary sections were compared according to the corresponding endothelial response to acetylcholine. Results: Sections with a decrease epicardial coronary arterial diameter in response to acetylcholine had smaller baseline lumen (7.5 (2.4) mm 2 vs 8.8 (3.3) mm 2, p = 0.006) but larger plaque burden (37.1% (9.4%) vs 31% (7%), p = 0.003) than sections with normal endothelial response. Sections with endothelial dysfunction had larger necrotic core plaques: 0.13 (0.03–0.33) mm 2 vs 0.0 (0.0–0.07), p<0.001 and more dense calcium: 0.03 (IQR 0.0–0.13) mm 2 vs 0.0 (0.0–0.10) mm 2, p<0.01), than those with normal endothelial response. Only necrotic core area was associated with endothelial dysfunction (p<0.001) after adjusting for other measures. Conclusions: This study suggests that local coronary endothelial dysfunction in patients with minimal coronary atherosclerosis is associated with plaque characteristics that are typical of vulnerable plaques.